Approach to the pediatric athlete with back pain: more than just the pars. Issue 4 (2nd October 2015) - Dizdarevic, Ismar; Bishop, Meghan; Sgromolo, Nicole; Hammoud, Sommer; Atanda, Alfred
Abstract: Back pain in a pediatric patient can present a worrisome and challenging diagnostic dilemma for any physician. Although most back pain can be attributed to muscle strains and poor mechanics, it is necessary to appreciate the full differential of etiologies causing back pain in the pediatric population. The physician must recognize areas of mechanical weakness in the skeletally immature spine and the sport specific forces that can predispose a patient to injury. A comprehensive history involves determining the onset, chronicity, and location of the pain. A focused physical exam includes a neurological exam as well as provocative testing. The combination of a thorough history and focused physical exam should guide appropriate imaging. Radiographic tests are instrumental in narrowing the differential, making a diagnosis, and uncovering associated pathology. Treatment modalities such as activity modification, heat/cold compresses, and NSAIDs can provide pain relief and allow for effective physical therapy. In most cases nonoperative methods are successful in providing a safe and quick return to activities. Failure of conservative measures requires referral to an orthopedic surgeon, as surgical intervention may be warranted.